SAT0461 Ultrasonography of salivary glands in primary sjogren's syndrome and association with disease activity, serological markers and biopsy of minor salivary glands. (12th June 2018) - Milic, V.; Radunovic, G.; Marinkovic, J.; Damjanov, N.
Abstract : Background: Parenchimal inhomogeneity of the salivary glands (SG) is the most relevant ultrasonografic (US) feature for diagnosis primary Sjogren's syndrome (pSS). Objectives: To analysis parechymal echostructure of SG in patients with established pSS and association USSG score with disease activity, serological markers and biopsy of minor salivary glands (MSG). Methods: This study included 205 pSS patients (mean age 53.9±11.5, disease duration 5.6 years) and 87 healthy controls (mean age 52.3±14.7). All pSS patients fulfilled the AECG diagnostic criteria. The disease activity was evaluated by EULAR SS disease activity index (ESSDAI), Sjögren's Syndrome Disease Damage Index (SSDDI) and EULAR Sjogren's syndrome patient reported index (ESSPRI). The presence of ANAs assessed by indirect immunofluorescence assay on Hep-2 cells, anti SSA and anti SSB (commercial ELISA kit) and RF (nephelometry). The parotid and submandibular glands on both sides were examined by US using a GE LogiqE9 with a linear high-frequency transducer (6–15 MHz). Inhomogeneity of the SG were graded according to the De Vita scoring system. Grading 0 was for a homogeneous gland, 1 for mild inhomogeinety, 2 for evident inhomogeneity and 3 for a grossly inhomogeous gland. The global SGUS score (0–6) was the sum of the scores of each pair of SG. Statistical analysis was performed by SPSS v19. Data were compared using t- test, χ² test and Mann-Whitney U test. The diagnostic accuracy of inhomogeneity was evaluated by area under the receiver operating characteristics curves (AUC-ROC). A multivariate linear regression analysis was performed to determine the factors associated with SGUS score. Results: Xerophtalmia and xerostomia were presented in 185/205 (90.2%) and 186/205 (91.2%), respectively. According to ESSDAI, the majority of pSS patients 88/205 (43%) had moderate disease activity. Seventy-eight per cent of pSS patients were anti-SSA positive, 44% anti-SSB positive. Biopsy of MSG was positive in 140/172 (81.4%) pSS patients. US abnormalities were established in 197/205 (96%) pSS patients and in 16/85 (18%) controls (p<0.0001). The median SGUS was significantly higher in pSS patients in comparison with control group [median (range) 4 (0–6) vs. 0 (0–2), p<0.0001]. The diagnostic accuracy of parenchymal inhomogeneity was high, AUC-ROC 0.89 (0.02) with cut-off ≥2 (Sp 89.5%, Sn 89.3%). Out of 197 pSS patients with abnormal findings, the most patients had US score 4 (47%), while 81% in control group had score 0. After adjustment for potential confounders variables, dry mouth (B=1.192, β=1.542; p=0.04), ESSDAI (B=0.184, β=1.203;p=0.008) and biopsy of MSG (B=1.006, β=2.735;p=0.05) were significantly associated with advanced US changes of SG. Dry eyes, SSDAI, ESSPRI and serological markers were not associated with USSG score (p>0.05). Conclusions: Our findings confirmed that parenchimal inhomogeneity of the salivary glands is the reliable feature for primary Sjogren's syndrome. Presence of xerostomia, objective disease activity assed by ESSDAI and pathological findings of biopsy of minor salivary glands had predictive value for advanced US change of salivary glands. Disclosure of Interest: None declared